Tuning Catalyst Activation and Utilization Via Controlled Electrode Patterning for Low‐Loading and High‐Efficiency Water Electrolyzers. Issue 14 (17th February 2022) - Yu, Shule; Li, Kui; Wang, Weitian; Xie, Zhiqiang; Ding, Lei; Kang, Zhenye; Wrubel, Jacob; Ma, Zhiwen; Bender, Guido; Yu, Haoran; Baxter, Jefferey; Cullen, David A.; et al.
Abstract: An anode electrode concept of thin catalyst‐coated liquid/gas diffusion layers (CCLGDLs), by integrating Ir catalysts with Ti thin tunable LGDLs with facile electroplating in proton exchange membrane electrolyzer cells (PEMECs), is proposed. The CCLGDL design with only 0.08 mgIr cm −2 can achieve comparative cell performances to the conventional commercial electrode design, saving ≈97% Ir catalyst and augmenting a catalyst utilization to ≈24 times. CCLGDLs with regulated patterns enable insight into how pattern morphology impacts reaction kinetics and catalyst utilization in PEMECs. A specially designed two‐sided transparent reaction‐visible cell assists the in situ visualization of the PEM/electrode reaction interface for the first time. Oxygen gas is observed accumulating at the reaction interface, limiting the active area and increasing the cell impedances. It is demonstrated that mass transport in PEMECs can be modified by tuning CCLGDL patterns, thus improving the catalyst activation and utilization. The CCLGDL concept promises a future electrode design strategy with a simplified fabrication process and enhanced catalyst utilization. Furthermore, the CCLGDL concept also shows great potential in being a powerful tool for in situ reaction interface research in PEMECs and other energy conversion devices with solid polymer electrolytes. Abstract : A catalyst‐coated liquid/gas diffusion layer (CCLGDL) with high catalyst utilization is designed and investigated around electrode pattern morphology impact on catalyst activation and utilization, and, as a powerful tool, CCLGDL enables visualization of in situ oxygen evolution with reaction at the electrode/membrane interface in proton exchange membrane electrolyzer cells for the first time.